1987
DOI: 10.1093/fampra/4.1.19
|View full text |Cite
|
Sign up to set email alerts
|

Experience of a Family Clinic at Benghazi, Libya, and Sociomedical Aspects of its Catchment Population

Abstract: The article highlights the pioneering efforts towards establishment of a family clinic as a model for provision of primary health care to the community at family level in Libya. Home visits were undertaken by health teams to introduce the clinic and record demographic and sociomedical data. Families were invited to attend the clinic for a complete health examination. It was largely a young population with an average family size of 7.1. The houses were generally overcrowded. The majority of the heads of familie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Indeed, in Tunisia, among 174 genetic diseases with an identified molecular defect, 73 (41.9%) are due to founder mutations (Romdhane and Abdelhak, 2011;Elloumi Zghal and Chaabouni Bouhamed, 2018;Romdhane et al, 2019). This high frequency of founder mutations could be explained by the high rates of inbreeding and endogamy that characterize NA populations: 34.04% in Algeria, 37.6% in Libya and 29.9% in Tunisia (Abudejaja et al, 1987;Zaoui and Biémont, 2002;Ben Halim et al, 2013). The most frequent form of intermarriage is between first cousins, particularly paternal first cousins and includes double first-cousin marriage (Ben Halim et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in Tunisia, among 174 genetic diseases with an identified molecular defect, 73 (41.9%) are due to founder mutations (Romdhane and Abdelhak, 2011;Elloumi Zghal and Chaabouni Bouhamed, 2018;Romdhane et al, 2019). This high frequency of founder mutations could be explained by the high rates of inbreeding and endogamy that characterize NA populations: 34.04% in Algeria, 37.6% in Libya and 29.9% in Tunisia (Abudejaja et al, 1987;Zaoui and Biémont, 2002;Ben Halim et al, 2013). The most frequent form of intermarriage is between first cousins, particularly paternal first cousins and includes double first-cousin marriage (Ben Halim et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…To analyse the data, one could begin with the average household size of 6.3, which is higher than that reported for the entire country, 5.89 (2006 census) but comparable with the only other study of a Libyan city, Benghazi, 6.5 (Abudejaja et al 1987;Salem and El-Haddad 2002). It is comparable also to some Arab countries like Kuwait and other developing nations, but is much higher than the household size of the developed world like North America and Europe, which does not exceed 3 (UN 2004).…”
Section: Discussionmentioning
confidence: 81%
“…This phenomenon seems to be frequently reported in highly inbred populations as described by Romdhaneet al (), where 75 disease associations were reported. While Libyan population is characterized by its heterogeneous ethnic background and high rate of consanguinity (Abudejaja et al, ), the report of multiple disease associations in the same individual could be expected. The main challenging consequence of comorbidity is undoubtedly the possibility of misdiagnosis especially when phenotypes are extremely rare and overlapping as one phenotype could be hidden by another (Romdhaneet al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In Egypt, among 48 patients clinically suspected to have FA, the diagnosis has been cytogenetically confirmed for 31 cases for whom the consanguinity rate reaches 97% (Temtamy et al, ). Jewish FA patients have been reported mostly from Morocco and Tunisia (Tamary et al, ).In Libya, the consanguinity rate reaches 37.6% in Benghazi (Abudejaja et al, ). Unfortunately, epidemiological studies for numerous cases including FA are lacking due to an unstructured health system.…”
Section: Introductionmentioning
confidence: 99%